МОДЕРНИЗАЦИЯ КИТАЯ С ТРАДИЦИОННОЙ ДАНЬЮ К ПРОШЛОМУ - Каскарауова, А.; Бектурганова, П. (Journal of Oriental Studies, 2016)
Мақалада Қытай өркениетінiң қазiргi даму кезеңін- дегі идеологиясы және жаңғырту үдерістерінде Қытай елінің көне дәстүрлерінің ықпалы қарастырылады. This article examines the ideological line of the current leadership, which is caused by a combination of modern culture and the finest achievements of traditional Chinese culture. Analyze the influence of the ancient traditions of China’s current model of China’s modernization.